Tall building: effect of opening on torsional rigidity of a 3-D core wall - Huang, Xia (2014)
Nowadays, high rise reinforced concrete (RC) buildings are increasingly popular due to its fast construction and flexible planning. As building height increases, importance of lateral force action rises exponentially. The effects of sway and ground shaking of buildings caused by wind load and earthquakes would affect durability and service performance of the structures. Since lateral sway governs design when buildings are designed beyond a certain height, a good understanding on behaviours of structures under both static and seismic effects is essential for building design.